Study on chemical, UV and gamma radiation-induced grafting of 2-hydroxyethyl methacrylate onto chitosan - Casimiro, M. H. (2005)
In the present study, 2-hydroxyethyl methacrylate has been grafted onto chitosan by using either chemical initiation, or photo-induction or gamma radiation-induced polymerisation, all under heterogeneous conditions. The evidence of grafting was provided by Fourier transform infrared spectroscopy and thermal analysis.